If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(19 + -2x) = 6(x + -6) (19 * 4 + -2x * 4) = 6(x + -6) (76 + -8x) = 6(x + -6) Reorder the terms: 76 + -8x = 6(-6 + x) 76 + -8x = (-6 * 6 + x * 6) 76 + -8x = (-36 + 6x) Solving 76 + -8x = -36 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 76 + -8x + -6x = -36 + 6x + -6x Combine like terms: -8x + -6x = -14x 76 + -14x = -36 + 6x + -6x Combine like terms: 6x + -6x = 0 76 + -14x = -36 + 0 76 + -14x = -36 Add '-76' to each side of the equation. 76 + -76 + -14x = -36 + -76 Combine like terms: 76 + -76 = 0 0 + -14x = -36 + -76 -14x = -36 + -76 Combine like terms: -36 + -76 = -112 -14x = -112 Divide each side by '-14'. x = 8 Simplifying x = 8
| 66-w=47 | | y^2+17y+c=0 | | -1(x+5)=3 | | n^2+10n+c=0 | | 18m-10=7m+9 | | x^2+19x+c=0 | | -9-9x^2+16x-7=0 | | p^2-11p+c=0 | | 744432668356579636562947593758572947c+675634586948366598366=75848485756693 | | y^2+.4y+c=0 | | 8.5/3= | | a+9/2=8 | | a^2-.26a+c=0 | | a^2-5a+c=0 | | 5x-2+2(2x+7)=-6(x+1) | | 25b-8=4b+34 | | a^2-.91a+c=0 | | y^2-.35y+c=0 | | -3(3x-5)+4x=5(x+6) | | -2x+6x-9=15 | | x^2-34x+c=0 | | 6(v-1)-3=-6(-3v+2)-3v | | x^2-42x+c=0 | | z^2-17z+c=0 | | y+1-5(-4y-1)=3(y-1) | | 5n^2-2n-7= | | x^2+7x+c=0 | | -4(x+1)=4x-7+2(2x+6) | | x^2-8x+22= | | 3x(2x-2)=3x(3x+5) | | a^2+1.69a+c=0 | | 4p+2=7p-6 |